2018
DOI: 10.1177/2325967118784518
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of Exercise-Induced Glenohumeral Cartilage Strain

Abstract: Background:The human shoulder joint is the most mobile joint in the body. While in vivo shoulder kinematics under minimally loaded conditions have been studied, it is unclear how glenohumeral cartilage responds to high-demand loaded exercise.Hypothesis:A high-demand upper extremity exercise, push-ups, will induce compressive strain in the glenohumeral articular cartilage, which can be measured with validated magnetic resonance imaging (MRI)–based techniques.Study Design:Descriptive laboratory study.Methods:Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The ability to assess early changes in cartilage composition may have implications for patient care and aid in therapeutic decision-making in several shoulder pathologies. This might be of considerably interest when counselling patients prone to early glenoid damage, e.g., overhead athletes 34 . Furthermore, rotator cuff tears lead to premature cartilage damage 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…The ability to assess early changes in cartilage composition may have implications for patient care and aid in therapeutic decision-making in several shoulder pathologies. This might be of considerably interest when counselling patients prone to early glenoid damage, e.g., overhead athletes 34 . Furthermore, rotator cuff tears lead to premature cartilage damage 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…The double-echo steady-state sequence is like the previously described MERGE sequence in that it provides high-resolution contrast between bone and cartilaginous structures. 1,2,10 In their investigation, Schleich et al 9 found sensitivity, specificity, and accuracy of 98%, 76.2%, and 95.9%, respectively, for the detection of labral tears. A large part of what makes the study by Higashihira et al 4 unique, and ultimately compelling, is the description of labral tear frequency relative to acetabular location.…”
Section: See Related Article On Page 2857mentioning
confidence: 98%